Is it possible to achieve waste free construction sites in Norway?. Issue 1 (October 2021) - Mamo Fufa, Selamawit; Venås, Christoffer; Kjendseth Wiik, Marianne
Abstract: The construction industry is one of the world's largest consumers of energy (ca. 40%) and natural resources (ca. 40%). Norwegian statistical data shows that waste from construction, rehabilitation and demolition is steadily increasing. Norway alone generated approximately 1.9 million tonnes of waste in 2017, around 1% more construction waste compared to 2016. Of this, only 34% of the waste was recycled, which is 8% less than in 2016, and 34% below the EU's requirements (70% reuse and recovery of all non-hazardous construction and demolition waste). There are on-going initiatives in Norway to address this and realise 'waste free' construction sites, with an ambition to contribute towards global, national and regional environmental impact reduction targets. The aim of this paper is to discuss challenges and opportunities for waste free construction sites in Norway and lessons learnt from Norwegian fossil and emission free construction sites. This paper concludes that Norwegian waste-free construction is ambitious but possible.